An Enhanced Flower Pollination Algorithm For Multiple Sequence Alignment - Hussein, Ahmad Moh’d Aziz Issa (2020)
Multiple sequence alignment (MSA) is an alignment of three or more sequences. Studies show that MSA exhibits a challenge, that is, how to find the MSA that maximises the Quality (Q) score and Total Column (TC) score. This problem is an NP-complete problem. Hence, numerous researchers have devoted their efforts to tackle the MSA problem, yet, there is still a shortcoming in the accuracy.